P619 Maintenance of efficacy following tofacitinib dose reduction in patients with ulcerative colitis in stable remission. (25th January 2019) - Rubin, D T; Travis, S; Abraham, B P; Su, C; Lawendy, N; Fan, H; Woodworth, D A; Thorpe, A J; Nduaka, C I; Quirk, D; Reinisch, W
Abstract: Background: Tofacitinib is an oral, small-molecule JAK inhibitor approved in several countries for the treatment of ulcerative colitis (UC). Safety and efficacy of tofacitinib 5 and 10 mg twice daily (BID) were evaluated in 2 Phase 3 induction studies (OCTAVE Induction 1 and 2, NCT01465763 and NCT01458951), a 52-week, Phase 3 maintenance study (OCTAVE Sustain, NCT01458574), and an ongoing open-label, long-term extension (OLE) study (NCT01470612). Here, we assess maintenance of remission following tofacitinib dose reduction from 10 mg BID in OCTAVE Sustain to 5 mg BID in the OLE study, and explore potential predictors of successful dose reduction. Methods: Patients in remission (total Mayo score ≤2 with no individual subscore >1, rectal bleeding subscore 0) at Wk52 of OCTAVE Sustain (central read) received tofacitinib 5 mg BID in the OLE study. We present remission rates (local read; as observed and with non-responder imputation) with tofacitinib 5 mg BID in the OLE study (as of 10 November 2017) among patients who achieved remission with tofacitinib 10 mg BID in OCTAVE Sustain, and evaluate characteristics of these patients, stratified by whether they subsequently maintained remission (local read; as observed) with 5 mg BID at Month (M)12 of the OLE study. Results: Of 76 patients treated with tofacitinib 10 mg BID who were in remission at Wk52 of OCTAVE Sustain and received 5 mg BID in the OLE study, 82% and 76% (as observed) were in remission at M12 and M24 of the OLE study, respectively (table). Patient characteristics by remission status at M12 of the OLE study are shown (table). Alternatively, by duration of remission in OCTAVE Sustain: among patients in remission at baseline (BL), Wk24 and Wk52 of OCTAVE Sustain (remission ≥12 months pre-dose reduction), 91% (21/23) maintained remission at M12 of the OLE study, vs. 82% (18/22) who were not in remission at OCTAVE Sustain BL but in remission at both Wk24 and Wk52 (remission 6–<12 months pre-dose reduction), and 71% (15/21) who were in remission at Wk52 but not Wk24, regardless of BL status (remission <6 months pre-dose reduction). Conclusions: In this post-hoc analysis, most patients with UC who achieved remission with tofacitinib 10 mg BID in OCTAVE Sustain and reduced to 5 mg BID in the OLE study maintained remission through M24 of the OLE study. Despite small pt numbers, maintenance of remission after dose reduction was numerically more likely for patients in remission for ≥6 months than for those in remission for <6 months prior to reduction. Further studies are needed to evaluate flexible dosing of tofacitinib in patients with UC.